Criminal Justice System Reform for Women as Victims of Domestic Violence Through Local Wisdom - Fatoni, Syamsul; Muti’ah, Dewi; Wijaya, Dodik Pranata (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2021)
The criminal justice system aiming to serve as a resolution of domestic violence should take into account the adat law system, religious law, and self-regulation living in society. Marriage Institution and Law Number 23 of 2004 concerning Abolishment of Domestic Violence turns out to be a criminogenic factor. This research seeks to investigate the criminal justice system linked to measures for the protection of women as victims of domestic violence in Indonesia and to find out and analyze the contribution of local wisdom to the reform of the system regarding the protection of female victims of domestic violence. This research required doctrines involving the study of secondary data supported by a field study and systematic analyses of the existence of the criminal justice system regarding domestic violence cases with an approach to the local wisdom in Madurese society. The research discovers that the criminal justice system in mitigating the female victims of domestic violence must be integrated and synergized with the sub-systems embracing police, health professionals, social workers, voluntary facilitators, and preachers assigned in criminal court as governed under the Law Number 23 of 2004. The presence of local wisdom in the reform of the criminal justice system concerning domestic violence cases represents the measures taken to shape criminal law in Indonesia by accommodating the values that live in societies, including religious teaching through restorative justice. This approach is intended to accommodate the interest of the victims and criminal offenders to resolve the issue within the criminal justice system.